Preparation and Catalytic Activity of BINOL‐Derived Silanediols. Issue 3 (11th December 2014) - Wieting, Joshua M.; Fisher, Thomas J.; Schafer, Andrew G.; Visco, Michael D.; Gallucci, Judith C.; Mattson, Anita E.
Abstract: Enantiopure silanediols derived from BINOL are an innovative family of stereoselective hydrogen‐bond donor (HBD) catalysts. Silanediols incorporated into a BINOL framework are attractive catalysts, as they are readily accessible and highly customizable. Structural modifications of the BINOL backbone affect the reactivity and selectivity of the silanediol catalysts in the additions of silyl ketene acetals to N ‐acyl isoquinolinium ions. The best results were obtained when the silanediol scaffold was substituted at the 4, 4′‐ and 6, 6′‐positions. This report includes details regarding the properties of selected BINOL‐based silanediol catalysts, including their acidities, binding constants, and X‐ray crystal structures. Abstract : A family of BINOL‐derived enantiopure silanediols has been prepared and studied. The effect of the substitution pattern of the BINOL backbone on catalyst performance is detailed. The acidities and chloride binding constants are also reported for this new and exciting class of hydrogen‐bond donor (HBD) catalysts.